ANALISIS KRITIS TERHADAP AMBANG BATAS PENCALONAN KEPALA DAERAH: PERSPEKTIF HUKUM DAN KEBIJAKAN PUBLIK - Arifin, Firdaus (Jurnal Ilmiah Dinamika Hukum, 2024)
The candidate threshold policy for regional heads in Indonesia aims to enhance candidate quality through significant political support. However, the implementation of this policy often negatively impacts political participation and competition at the local level. This study aims to analyze the effects of the candidate threshold policy on the number of candidates, the dominance of major parties, and the quality of local democracy. The research employs legal research methods, including literature review and policy analysis with a qualitative approach. The findings indicate that the threshold policy leads to a decrease in the number of candidates, strengthens the dominance of major parties, and reduces healthy political competition. Recommended policy reforms include lowering the threshold, providing support for independent candidates, increasing transparency, conducting periodic evaluations, and enhancing political education. The implications of these findings highlight the need for policy adjustments to create a more equitable and effective election process and to strengthen the quality of local democracy.